Pengaruh metode Qiraat dalam memahami makna dan hikmah dalam Al-Qur’an - Nadiya, Nadiya (Maliki Interdisciplinary Journal, 2024)
This study aims to investigate the effects of the Qiraat method on understanding the meaning and wisdom of the Al-Quran. The Al-Quran holds great significance as the holy book for Muslims, and the Qiraat method is employed to read and comprehend its text. Utilizing a comparative analytical approach, this research examines various Qiraat methods, including Qiraat Hafs ’an ’Asim, Qiraat Warsh ’an Nafi’, among others. Additionally, it involves an analysis of the textual content of the Al-Quran, linguistic theories, and interpretative approaches to delve into the profound meanings and wisdom encapsulated within. The research methodology employed entails the collection of data from primary and secondary sources, encompassing Qiraat books, Quranic exegesis, and related scholarly works. Subsequently, the collected data are subjected to comparative analysis, with the aim of identifying divergences and convergences in the interpretation and understanding of the Al-Quran based on distinct Qiraat methods. The anticipated outcome of this research is to furnish a comprehensive understanding of how the Qiraat method influences the comprehension of the meaning and wisdom within the Al-Quran. Moreover, the study aims to offer fresh insights into the diverse interpretations of the Al-Quran, influenced by the implementation of distinct Qiraat methods. It is hoped that the findings will contribute to the development of a more holistic and profound understanding of the Al-Quran among the Muslim community.